A Clinical Study to Evaluate the Effect of Nimba Twak Kashaya Prakshalana In Kaphaja Yoni Vyapat w.s.r to Vulvo Vaginal Candidiasis (Candida Albicans) (International Journal of Ayurveda and Pharma Research, 2022)
Kaphaja Yoni Vyapat is described as a condition where symptoms like Picchila and Sheetala discharge from vagina occurs with Kandu, Mandaruja, Artava-dushti and Pandu. The symptoms of Kaphaja Yoni Vyapat mentioned in Ayurvedic literature appears similar to the clinical features of vulvo vaginal candidiasis. It is the second most common infection among women in reproductive age group with a single incidence of 75%, and two or more episodes in 45% of women. Candida albicans is responsible for 85% to 90% of the vaginal yeast infections. Here an attempt was done to screen, isolate and treat the diagnosed cases of Kaphaja Yoni Vyapat w.s.r to Candida albicans through Nimba Twak Kashaya & Triphala Kashayaprakshalana. The objective of this study was to evaluate the efficacy of Nimba Twak Kashaya Prakshalana and to compare it with Triphala Kashaya Prakshalana in Kaphaja Yoni Vyapat. 63.09% had complete relief from yoni Srava, 97.9% had complete relief from Yoni kandu, 100% had relief from Yoni vedana, 93.99% had complete relief from vulval rashes, 76.88% had normal vaginal pH, 95% had no candida in vaginal wet mount. Overall 88.23% showed improvement in Group A and 87.38% showed improvement in Group B. Nimba & Triphala has Tikta and Kashaya rasa, Kaphahara, Krimighna, Kandughna and Grahi properties. It has anti-fungal & anti-pruritic action also.Thus Prakshalana with above said drugs directly acted on the vaginal mucosa and enabled easier target specific action and did the inhibitory action against growth of candida albicans.